2020
DOI: 10.1002/bse.2496
|View full text |Cite
|
Sign up to set email alerts
|

Can entrepreneurial orientation improve sustainable development through leveraging internal lean practices?

Abstract: This study aims to examine the mediating role of internal lean practices (ILPs) on the relationship between entrepreneurial orientation and triple bottom line performance (i.e. environmental, social, and operational performance). We examine Chile, which represents a vibrant economy and one of the world's most productive entrepreneurship ecosystems but with a history of socio‐economic inequalities and strong profit‐driven pressures to overextract natural resources. The study is based on a questionnaire related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
76
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 62 publications
(87 citation statements)
references
References 107 publications
2
76
0
1
Order By: Relevance
“…Many scholars argue innovation and LPs may be complimentary. LPs are known to help reduce waste and contribute to the environmental dimension of TBL while driving operational excellence (Cherrafi et al, 2017;King and Lenox, 2001;Kumar and Rodrigues, 2020;Chavez et al, 2020). Lean is more related to incremental rather than radical innovation (Abdallah et al, 2019); though in some cases it can drive radical innovation (Kim et al, 2012).…”
Section: 2!fits Between Lps and Innovativenessmentioning
confidence: 99%
See 4 more Smart Citations
“…Many scholars argue innovation and LPs may be complimentary. LPs are known to help reduce waste and contribute to the environmental dimension of TBL while driving operational excellence (Cherrafi et al, 2017;King and Lenox, 2001;Kumar and Rodrigues, 2020;Chavez et al, 2020). Lean is more related to incremental rather than radical innovation (Abdallah et al, 2019); though in some cases it can drive radical innovation (Kim et al, 2012).…”
Section: 2!fits Between Lps and Innovativenessmentioning
confidence: 99%
“…Achieving TBL means firms need not only create value for shareholders, but also protect the environment around and the lives of the people they serve (Wu et al, 2015). While LPs can decrease cost by reducing waste, it must reduce impacts to both the environment and society (Chavez et al, 2020;Dhingra et al, 2014). It has been suggested that synergies can be obtained by simultaneously addressing all three TBL dimensions using innovative ideas (Pagell and Wu, 2009).…”
Section: 3!the Fit-as-mediation Modelmentioning
confidence: 99%
See 3 more Smart Citations